Strategi Pemasaran Agrowisata Belantih Coffee Farm di Desa Belantih Kecamatan Kintamani Kabupaten Bangli (Jurnal Agribisnis dan Agrowisata, 2025)
Marketing Strategy of Belantih Coffee Farm Agrotourism in Belantih Village, Kintamani District, Bangli Regency. Seeing that the marketing activities that have not been optimized by the agro-tourism manager have caused a decrease in visitors to Belantih Coffee Farm Agrotourism, so that this company can again increase the number of tourist visits, an appropriate marketing strategy formulation is needed. This study aims to identify internal and external factors, alternative strategies, and formulate the right marketing strategy for Belantih Coffee Farm Agrotourism using IE and SWOT matrix analysis. This research was conducted in Belantih Village, Kintamani District, Bangli Regency from April to June 2023. This research is a type of qualitative and quantitative research. Based on the results of the SWOT matrix analysis, there are 5 alternative strategies that can be carried out by agritourism parties, namely through the SO, WO, ST, and WT strategies. The SO strategy is to expand the market by highlighting the advantages of existing products and tourist attractions, utilizing advances in information technology in conducting promotional activities through Instagram social media. The WO strategy is to optimize promotional activities at Belantih Coffee Farm Agrotourism with technology well to reach a wider target market. The ST strategy is to develop a more attractive tourism concept for visitors. The WT strategy is to add tourist attractions such as photo spots, outbound, home stays and other attractions so as not to lose competitiveness with other tourist attractions.
Keywords: strategy; belantih coffee farm agrotourism; marketing